Recovery of Prenatal Baicalein Exposure Perturbed Reproduction by Postnatal Exposure of Testosterone in Male Mice - Sridevi Vaadala; Naveen Ponneri; Venkata Shashank Karanam; Sri Bhashyam Sainath; Pamanji Sreenivasuala Reddy; Ramachandra Reddy Pamuru; Arifullah Mohammed (International Journal of Endocrinology)
Baicalein (BC), a flavonoid, which lacks the qualities of reproductive health and shows adverse effects, is tested in this study. Inseminated mice were injected with 30, 60, and 90 mg BC/Kg body weight on gestation days 11, 13, 15, and 17. The F1 BC-exposed males of each dosage were divided into six groups. First three groups (n = 6 from each BC dosage) were used for assessment of reproductive performance, the others (n = 4 from each BC dosage) were administered with testosterone 4.16 mg/kg body weight on postnatal days 21, 31, and 41. The reproductive health of adult F1 males at the age of 55 and 60 was tested. Prenatal BC exposure showed reduced fertility after cohabitation with control females. The BC exposure significantly reduced the body weight, tissue indices, and sperm parameters (motility, count, viability, and daily sperm count) and altered the sperm membrane in a hypoosmotic swelling test. A downward trend was observed in testicular steroidogenic marker enzymes (3β- and 17β-steroid dehydrogenases) and serum testosterone, whereas increase in serum titers of FSH and LH along with altered the testicular histology. Conversely, testosterone (4.16 mg/kg body weight) partially recovered reduced male reproductive health by BC. BC impaired male reproductive health due to low levels of testosterone is reverted by external testosterone is evidenced in this study.